Challenges for the North Maine Woods - Irland, Lloyd (Maine Policy Review, 1991)
Lloyd Irland discusses the rapid changes in the value of Maine’s forests as perceived by the public, the threats to those values, the policy tools for managing those conflicts, and the ways of paying for forest benefits. He notes that regulation is destined to lay a larger role in the policy mix for these new forest values.